Mechanical and fatigue strength assessment of friction stir welded plates of magnesium alloy AZ31B - Luna, Carlos Fernando; Arenas, Fernando Franco; Pereira, Victor Ferrinho; Ávila, Julián Arnaldo [UNESP] (FapUNIFESP (SciELO), 2018)
Light-alloys play a significant role in saving weight in automotive and aerospace industries; however, a few joining methods guarantee mechanical and fatigue strengths for high performance application. Even conventional arc welding processes do not offer constant quality joints. Therefore, this study uses an alternative solid-state welding process, friction stir welding (FSW), to analyze post processing microstructures and assess mechanical and fatigue strength. Magnesium alloy AZ31B plates were welded using different welding parameters in a dedicated FSW machine. The effect of the spindle speed (ω) and welding speed (ν) on the microstructure, the tensile strength and fatigue were studied. The stirred zone (SZ) at the FS-welded joints presented a microstructure composed by homogeneous equiaxial grains, refined by dynamic recrystallization. A rise in grain size, weld bead width, tensile and fatigue strengths with the increase of speed ratio (ω/ν) were observed. Results of the fatigue and mechanical strength here presented outperformed results from welds made with conventional milling machines.
Avaliação da resistência mecânica e à fadiga de chapas soldadas por atrito com pino não consumível da liga de magnésio AZ31B
Keywords: Fatigue strength; Friction stir welding; FSW; Magnesium AZ31B; Tensile strength